An ordered mesoporous molybdenum disulfide material, its preparation method and application

Ordered mesoporous molybdenum disulfide was prepared by solvent evaporation-induced self-assembly of amphiphilic polymer block copolymers and ammonium tetrathiomolybdate, solving the synthesis problem in the prior art and improving the orderliness and performance of the material.

CN117023638BActive Publication Date: 2025-10-31SOUTHEAST UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311103310.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-30
Publication Date
2025-10-31
Estimated Expiration
2043-08-30

AI Technical Summary

Technical Problem

Existing technologies make it difficult to easily synthesize ordered mesoporous molybdenum disulfide materials, and the degree of order in their mesoporous structure is not high, which affects their catalytic, adsorption, and sensing performance.

Method used

An ordered mesoporous molybdenum disulfide material was prepared by using an amphiphilic polymer block copolymer as a template agent and ammonium tetrathiomolybdate as an inorganic precursor to form an ordered mesoscopic structure through solvent evaporation induced self-assembly (EISA) followed by calcination under an Ar/H2 atmosphere.

Benefits of technology

This study achieved a high specific surface area and abundant adsorption active sites in ordered mesoporous molybdenum disulfide materials, thereby improving their performance in catalysis, sensing and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117023638B_ABST
    Figure CN117023638B_ABST
Patent Text Reader

Abstract

This invention provides an ordered mesoporous molybdenum disulfide material, its preparation method, and its applications. The invention employs an amphiphilic block copolymer and ammonium tetrathiomolybdate in a DMF / H₂O dual-solvent system for co-assembly, followed by self-assembly to form an ordered mesoscopic structure as the solvent evaporates. After high-temperature calcination of the composite film in an Ar / H₂ atmosphere, the template agent decomposes, and the ammonium tetrathiomolybdate decomposes into molybdenum disulfide, yielding the ordered mesoporous molybdenum disulfide material. The semiconductor gas sensor based on this ordered mesoporous molybdenum disulfide material exhibits excellent sensing performance for NO₂ gas at room temperature, including high sensitivity, fast response-recovery speed, and high selectivity, surpassing most previous reports. It holds promise for applications in atmospheric environmental monitoring, smart healthcare, and other fields. The preparation process of this invention is simple, reproducible, and easily controlled, with adjustable preparation parameters, facilitating industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an ordered mesoporous molybdenum disulfide material, its preparation method and application, belonging to the field of advanced nanoporous materials. Background Technology

[0002] In recent years, transition metal chalcogenides have attracted widespread attention in fields such as electronic devices, photocatalysis, and gas sensing (see [link to article]). Nat. Nanotech ., 2011, 6, 147−150.; Mater. Today Sustain. ,2021, 13, 100073.; ACS Nano , 2013, 7, 6, 4879−4891.; Small , 2018, 14 (36). Molybdenum disulfide (MoS2), as the most widely studied transition metal chalcogenide, possesses a graphene-like two-dimensional layered structure, a large specific surface area, and high carrier mobility, which significantly influence its related application performance (see [reference]). Nat. Chem (., 2013, 5, 263−275.). Preparing molybdenum disulfide materials with ordered mesoscopic structures can further increase their specific surface area, greatly promoting the transport and diffusion rates of substances within the material, and further enhancing their catalytic, adsorption, and sensing properties. Therefore, related research on preparation and application is of great significance. Currently, mesoporous molybdenum disulfide is mainly synthesized via hydrothermal / solvothermal methods (see...). New J. Chem (., 2014, 38, 2379−2385.). However, this method is rather cumbersome and the resulting mesoporous structures are not highly ordered. Therefore, developing a simple, convenient, one-step method for synthesizing ordered mesoporous molybdenum disulfide is of great significance. Summary of the Invention

[0003] Objectives of the Invention: The first objective of this invention is to provide an ordered mesoporous molybdenum disulfide material; the second objective is to provide a method for preparing the ordered mesoporous molybdenum disulfide material; and the third objective is to provide the application of the ordered mesoporous molybdenum disulfide material in the preparation of gas sensors, photocatalysis, and photoelectric detection.

[0004] Technical Solution: The present invention discloses a method for preparing ordered mesoporous molybdenum disulfide material. The method uses an amphiphilic polymer block copolymer as an organic template agent, ammonium tetrathiomolybdate ((NH4)2MoS4) as an inorganic precursor, and DMF and / or H2O as solvents. Solvent evaporation-induced self-assembly (EISA) is used to allow the template agent and inorganic precursor to react and form microphase separation, resulting in an ordered mesoscopic structure, thereby synthesizing ordered mesoporous molybdenum disulfide. The hydrophobic segments of the amphiphilic polymer block copolymer aggregate in the solvent to form spherical micelles with hydrophobic segments as the core and hydrophilic segments of the amphiphilic polymer block copolymer as the shell. Calcination under an Ar / H2 atmosphere promotes the decomposition of ammonium tetrathiomolybdate into molybdenum disulfide, while simultaneously removing the template agent, to obtain the ordered mesoporous MoS2 material.

[0005] Furthermore, the hydrophilic segment of the amphiphilic block copolymer has a molecular weight of 2500-5000 g / mol, and the hydrophobic segment has a molecular weight of 2500-37500 g / mol.

[0006] Furthermore, the amphiphilic block copolymer is polystyrene-polyethylene oxide (PS-) b -PEO), polybutadiene-polyethylene oxide (PB- b -PEO), polystyrene-poly4-vinylpyridine (PS- b -P4VP), polyethylene oxide-polymethyl methacrylate (PEO- b -PMMA), polyacrylic acid-polystyrene (PAA- b One or more of the following: -PS).

[0007] Furthermore, the preparation method of the ordered mesoporous molybdenum disulfide material of the present invention includes the following steps:

[0008] (1) The amphiphilic block copolymer (M n = 10000-30000 g / mol) is dissolved in N,N-dimethylformamide and stirred to obtain solution A; ammonium tetrathiomolybdate is dissolved in deionized water and stirred to obtain solution B; solution A and solution B are mixed and stirred to obtain transparent colloidal solution C;

[0009] (2) Transfer the transparent colloidal solution C to a petri dish, evaporate it, dry and solidify it to obtain an organic-inorganic composite membrane. Scrape the organic-inorganic composite membrane off the petri dish, grind it, and obtain powder.

[0010] (3) The powder obtained in step (2) is placed in a tube furnace and calcined under an Ar / H2 atmosphere to obtain an ordered mesoporous molybdenum disulfide material.

[0011] Further, in step (1), the mass ratio of the amphiphilic block copolymer to ammonium tetrathiomolybdate is 1:2 to 1:4.

[0012] Further, in step (1), the volume ratio of deionized water to N,N-dimethylformamide is 1:5 to 1:50.

[0013] Furthermore, in step (2), the evaporation temperature is 40-60 ℃ and the evaporation time is 12-24h.

[0014] Furthermore, in step (2), the drying and curing temperature is 100-150 ℃, and the drying and curing time is 12-24 h.

[0015] Further, in step (3), the calcination under the Ar / H2 atmosphere is to first heat the temperature to 350-500 ℃ at a heating rate of 5-10℃ / min and calcine for 1-3 h, wherein the Ar / H2 atmosphere is the volume ratio of argon to hydrogen of 50:20.

[0016] The ordered mesoporous molybdenum disulfide material obtained by the preparation method described in this invention.

[0017] Furthermore, the ordered mesoporous tungsten disulfide material of the present invention has a pore size of 5-40 nm and a wall thickness of 2-10 nm between mesopores.

[0018] The present invention also includes the application of the ordered mesoporous molybdenum disulfide material described herein in the preparation of gas sensors, photocatalysis, and photoelectric detection.

[0019] This invention can effectively control the mesopore size and specific surface area of ​​the material by controlling the molecular weight of the hydrophobic blocks of the block copolymer; and can control the wall thickness of the synthesized ordered mesoporous molybdenum disulfide material by changing the length of the hydrophilic blocks of the amphiphilic block copolymer.

[0020] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:

[0021] (1) The method for synthesizing structure-oriented ordered mesoporous molybdenum disulfide materials using amphiphilic block copolymers in this invention is universal and applicable to a variety of amphiphilic block copolymers (such as PS- b -PEO, PB- b -PEO, PS- b -P4VP、PEO- b -PMMA, PAA- b -PS, etc.).

[0022] (2) In this invention, the method of in-situ carbonization using a template agent to synthesize ordered mesoporous transition metal chalcogenides has universality. It utilizes the decomposition of ammonium tetrathiomolybdate into metal sulfides at a certain temperature, combined with sp... 2 The PS segment of the hybrid carbon-carbon double bond is transformed in situ into amorphous carbon as a rigid support for the transition metal sulfide, thereby obtaining a highly ordered transition metal chalcogenide material with a high specific surface area. Any method that uses the self-assembly principle to synthesize ordered mesoporous transition metal chalcogenide materials is applicable.

[0023] (3) This invention differs from previous methods for synthesizing ordered mesoporous transition metal chalcogenides by directly employing a method of co-assembling ammonium tetrathiomolybdate with ammonium tetrathiomolybdate. Because the hydrophilic blocks in the block copolymer can bind with ammonium tetrathiomolybdate through "hydrophilic-hydrophilic interaction", they form uniform spherical micelles, which then self-assemble into an ordered mesoscopic structure during subsequent solvent evaporation.

[0024] (4) The ordered mesoporous molybdenum disulfide material prepared by the present invention has a large specific surface area, abundant adsorption active sites, high crystallinity, controllable pore size and pore wall thickness, and is expected to be widely used in catalysis, sensing, energy and other fields. Attached Figure Description

[0025] Figure 1 The image shows a SEM image of the ordered mesoporous molybdenum disulfide material prepared in Example 1.

[0026] Figure 2 High-resolution TEM image of the ordered mesoporous molybdenum disulfide material prepared in Example 1.

[0027] Figure 3 The image shows the XRD pattern of the ordered mesoporous molybdenum disulfide material prepared in Example 1.

[0028] Figure 4 The image shows the Raman spectrum of the ordered mesoporous molybdenum disulfide material prepared in Example 1.

[0029] Figure 5 The image shows the room temperature NO2 gas sensing performance test results of the ordered mesoporous molybdenum disulfide material prepared in Example 1. Detailed Implementation

[0030] The technical solution of the present invention will be further described below with reference to the accompanying drawings.

[0031] The reagents used in the following experiments:

[0032] Ammonium tetrathiomolybdate ((NH4)2MoS4) and N,N-dimethylformamide were purchased from Shanghai Aladdin Reagent Company; the amphiphilic block copolymer polystyrene-polyethylene oxide (PS- b-PEO), polybutadiene-polyethylene oxide (PB- b -PEO), polystyrene-poly4-vinylpyridine (PS- b -P4VP), polyethylene oxide-polymethyl methacrylate (PEO- b -PMMA), polyacrylic acid-polystyrene (PAA- b -PS) were all purchased from Polymer Source in the United States.

[0033] Example 1: Preparation of Ordered Mesoporous Molybdenum Disulfide Materials

[0034] (1) 0.10 g of polystyrene-polyethylene oxide (PS-) b -PEO, M n = 20000 g mol -1 Dissolve 0.20 g of ammonium tetrathiomolybdate ((NH4)2MoS4) in 5 mL of DMF and stir to obtain a homogeneous solution A; dissolve 0.20 g of ammonium tetrathiomolybdate ((NH4)2MoS4) in 1 mL of H2O and stir to obtain a homogeneous solution B; mix solution A and solution B and stir to obtain a reddish-black transparent colloidal solution C.

[0035] (2) The reddish-black transparent colloidal solution C was transferred to a petri dish and evaporated at 40 °C for 12 h. The petri dish was then transferred to an oven at 100 °C for further solvent evaporation and solidification for 24 h to obtain a transparent organic-inorganic composite film. The organic-inorganic composite film was scraped off the petri dish to obtain a black powder.

[0036] (3) The black powder obtained in step (2) was placed in a tube furnace and calcined at 400℃ for 2 h in an Ar / H2 (50 / 20 sccm) atmosphere with a heating rate of 10.0 ℃ / min to obtain black ordered mesoporous MoS2 material.

[0037] The ordered mesoporous MoS2 material prepared in this embodiment was analyzed by scanning electron microscopy, and the results are as follows: Figure 1 As shown. Figure 1 Here is a SEM image of the ordered mesoporous molybdenum disulfide material prepared in Example 1. Figure 1 It can be seen that the ordered mesoporous molybdenum disulfide material prepared in this embodiment has a highly ordered mesoporous structure with a pore size of about 20 nm and a pore wall thickness of about 5 nm.

[0038] The ordered mesoporous MoS2 material prepared in this embodiment was analyzed by high-resolution transmission electron microscopy, and the results are as follows: Figure 2 As shown. Figure 2 Here is an HRTEM image of the ordered mesoporous molybdenum disulfide material prepared in Example 1. Figure 2It can be observed that the ordered mesoporous MoS2 material prepared in this embodiment has clear lattice stripes, indicating that the MoS2 nanosheets are highly crystallized and form pore walls around the mesopores.

[0039] X-ray diffraction analysis was performed on the ordered mesoporous MoS2 material prepared in this embodiment, and the results are as follows: Figure 3 As shown. Figure 3 The image shows the XRD pattern of the ordered mesoporous molybdenum disulfide material prepared in Example 1. Figure 3 It can be seen that the ordered mesoporous MoS2 material prepared in this embodiment shows two obvious diffraction peaks, which correspond to the (100) and (110) crystal planes of molybdenum disulfide (PDF#37-1492), respectively, indicating that a highly crystalline mesoporous molybdenum disulfide material was obtained.

[0040] Raman spectroscopy analysis was performed on the ordered mesoporous MoS2 material prepared in this embodiment, and the results are as follows: Figure 4 As shown. Figure 4 The image shows the Raman spectrum of the ordered mesoporous molybdenum disulfide material prepared in Example 1. Figure 4 It can be observed that the ordered mesoporous MoS2 material prepared in this embodiment has E 1 2g and A 1 g Two distinct characteristic scattering peaks prove that pure MoS2 material has been obtained. Example 2

[0041] (1) Take 0.10 g PEO- b -PMMA (Mn = 25000 g mol) -1 Dissolve 0.30 g of ammonium tetrathiomolybdate ((NH4)2MoS4) in 9 mL of DMF and stir to obtain a homogeneous solution A; dissolve 0.30 g of ammonium tetrathiomolybdate ((NH4)2MoS4) in 1 mL of H2O and stir to obtain a homogeneous solution B; mix solutions A and B and stir to obtain a reddish-black transparent colloidal solution C. (2) Transfer the reddish-black transparent colloidal solution C to a petri dish and evaporate it at 40 °C for 12 h. Transfer the petri dish to a 100 °C oven to further evaporate the solvent and cure it for 24 h to obtain a transparent organic-inorganic composite membrane. Scrape the organic-inorganic composite membrane off the petri dish to obtain a black powder.

[0042] (3) The black powder obtained in step (2) was placed in a tube furnace and calcined at 450°C for 1.5 h under an Ar / H2 (50 / 20 sccm) atmosphere with a heating rate of 10.0°C / min to obtain black ordered mesoporous MoS2 material. Example 3

[0043] (1) Take 0.10 g PAA- b-PS (Mn = 30000 g mol) -1 Dissolve 0.40 g of ammonium tetrathiomolybdate ((NH4)2MoS4) in 10 mL of DMF and stir to obtain a homogeneous solution A; dissolve 0.40 g of ammonium tetrathiomolybdate ((NH4)2MoS4) in 2 mL of H2O and stir to obtain a homogeneous solution B; mix solution A and solution B and stir to obtain a reddish-black transparent colloidal solution C.

[0044] (2) The reddish-black transparent colloidal solution C was transferred to a petri dish and evaporated at 40 °C for 12 h. The petri dish was then transferred to an oven at 100 °C for further solvent evaporation and solidification for 24 h to obtain a transparent organic-inorganic composite film. The organic-inorganic composite film was scraped off the petri dish to obtain a black powder.

[0045] (3) The black powder obtained in step (2) was placed in a tube furnace and calcined at 500°C for 1.5 h in an Ar / H2 (50 / 20 sccm) atmosphere with a heating rate of 10.0°C / min to obtain black ordered mesoporous MoS2 material. Example 4

[0046] (1) Take 0.10 g PS- b -P4VP (Mn = 27000 g mol) -1 Dissolve 0.25 g of ammonium tetrathiomolybdate ((NH4)2MoS4) in 1 mL of H2O and stir to obtain a homogeneous solution B; mix solutions A and B and stir to obtain a reddish-black transparent colloidal solution C.

[0047] (2) The reddish-black transparent colloidal solution C was transferred to a petri dish and evaporated at 40 °C for 12 h. The petri dish was then transferred to an oven at 100 °C for further solvent evaporation and solidification for 24 h to obtain a transparent organic-inorganic composite film. The organic-inorganic composite film was scraped off the petri dish to obtain a black powder.

[0048] (3) The black powder obtained in step (2) was placed in a tube furnace and calcined at 350°C for 3 h in an Ar / H2 (50 / 20 sccm) atmosphere with a heating rate of 10.0°C / min to obtain black ordered mesoporous MoS2 material. Example 5

[0049] The ordered mesoporous molybdenum disulfide material obtained in Example 1 was used to fabricate a semiconductor gas sensor, and its comprehensive gas sensing performance was tested. Specifically, 0.1 g of ordered mesoporous molybdenum disulfide powder was thoroughly ground (for 1 minute), and 1 mL of ethanol was added to form a slurry. This slurry was then brushed onto an alumina ceramic tube with a gold electrode, and a Pt electrode was attached. The tube was placed in the instrument's test chamber (1.8 L), and the resistance of the ordered mesoporous molybdenum disulfide material was automatically recorded in real time by a Xiaoyu Electronics M2.0 gas-sensitive testing instrument. At the start of the test, several concentrations (2 ppm, 5 ppm, 10 ppm, 20 ppm, 50 ppm, 100 ppm, 200 ppm, 500 ppm) of dry NO2 gas were injected using a syringe. The resistance began to change. Once the resistance stabilized, the cap was opened, exposing the ordered mesoporous molybdenum disulfide material to air, and the resistance returned to its initial value. In this test, the sensitivity (responsivity) of the ordered mesoporous molybdenum disulfide thin film material was defined as S = (R0 / R0)0. a -R g ) / R a , where R a and R g These are the resistivity values ​​of the ordered mesoporous molybdenum disulfide material in air and the test gas, respectively. The response-recovery time is defined as the time required for 90% of the resistance change to be completed. The results are as follows: Figure 5 As shown.

[0050] Figure 5 The following are test results of the room temperature NO2 gas sensing performance of the ordered mesoporous molybdenum disulfide material prepared in Example 1: (a) is the dynamic response-recovery curve of the ordered mesoporous molybdenum disulfide material obtained in Example 1 to different concentrations (2-500 ppm) of NO2 at room temperature; (b) is the response value of the ordered mesoporous molybdenum disulfide material obtained in Example 1 to different concentrations (2-500 ppm) of NO2 at room temperature. (c) is the response-recovery time diagram of the ordered mesoporous molybdenum disulfide material obtained in Example 1 to 50 ppm NO2 at room temperature; (d) is the cyclic response-recovery test diagram of the ordered mesoporous molybdenum disulfide material obtained in Example 1 to 50 ppm NO2 at room temperature; (e) is the response value diagram of the ordered mesoporous molybdenum disulfide material obtained in Example 1 to 50 ppm of different types of gases (ammonia, methanol, ethanol, acetone, formaldehyde, styrene, benzene, toluene, carbon monoxide, hydrogen, methane, nitric oxide, and nitrogen dioxide) at room temperature; (f) is a comparison diagram of the room temperature NO2 gas sensing performance of the ordered mesoporous molybdenum disulfide material obtained in Example 1 and the materials reported in the literature (three-layer WSe2 film, few-layer MoS2, MoS2 nanosheets, MoS2@WS2 heterojunction, MoS2-graphene fiber, etc.).

[0051] Depend on Figure 5As can be seen from (a) and (b), the ordered mesoporous molybdenum disulfide material prepared in Example 1 gradually increases in sensitivity and tends to saturate with increasing NO2 concentration, with a sensitivity of S=44% to 50 ppm NO2.

[0052] Depend on Figure 5 As can be seen from (c) and (d), the ordered mesoporous molybdenum disulfide material sensor prepared in Example 1 has response-recovery times of 17 s and 52 s for 50 ppm NO2, respectively, and the sensor also has good cyclic stability.

[0053] Depend on Figure 5 (e) As can be seen, the ordered mesoporous molybdenum disulfide material sensor prepared in Example 1 has a sensitivity of S=44% to 50 ppm NO2, and its sensitivity to other gases is less than 6%, indicating that the sensor has high selectivity to NO2.

[0054] Figure 5 (f) shows the room-temperature NO2 gas sensing performance of the ordered mesoporous molybdenum disulfide material (mesoporous MoS2) obtained in Example 1, compared with the literature ACS Appl. Mater. Interfaces 2018, 10, 28, 23910-23917 (trilayer WSe2 film), ACSNano 2013, 7 (6), 4879-4891 (few-layer MoS2), ACS Nano 2015, 9 (9), 9314-9321 (MoS2 nanosheets), ACS Sensors 2017, 2 (11), 1744-1752 (MoS2, MoS2 (under UV light)), Sensor. Actuator. B Chem. 333 (2) (2021) 129571 (WSe2), J. Mater. Chem. A 2019, 7,14602-14612 (MoS2@WS2 heterojunction); The reported values ​​are compared. In this figure, the horizontal axis represents NO2 concentration, and the vertical axis represents sensitivity. Figure 5 (f) It can be seen that the NO2 gas-sensing performance of the ordered mesoporous MoS2 prepared in Example 1 is significantly better than that of other types of transition metal chalcogenide materials.

Claims

1. A method for preparing an ordered mesoporous molybdenum disulfide material, characterized in that, The preparation method uses an amphiphilic polymer block copolymer as an organic template agent, ammonium tetrathiomolybdate as an inorganic precursor, and DMF and H2O as solvents. Solvent evaporation induces self-assembly, causing the template agent and inorganic precursor to react and form a microphase separation, resulting in an ordered mesoporous structure, thus synthesizing ordered mesoporous molybdenum disulfide. The hydrophobic segments of the amphiphilic polymer block copolymer aggregate in the solvent, forming spherical micelles with hydrophobic segments as the core and hydrophilic segments of the amphiphilic polymer block copolymer as the shell. Calcination under an Ar / H2 atmosphere decomposes the ammonium tetrathiomolybdate into molybdenum disulfide, simultaneously removing the template agent, yielding mesoporous MoS2 material. The preparation method of the ordered mesoporous molybdenum disulfide material includes the following steps: (1) Dissolve the amphiphilic block copolymer in N,N-dimethylformamide and stir to obtain solution A; dissolve ammonium tetrathiomolybdate in deionized water and stir to obtain solution B; mix solution A and solution B and stir to obtain transparent colloidal solution C; the mass ratio of the amphiphilic block copolymer to ammonium tetrathiomolybdate is 1:2 to 1:4, and the volume ratio of deionized water to N,N-dimethylformamide is 1:5 to 1:

50. (2) Transfer the transparent colloidal solution C to a petri dish, evaporate it, dry and solidify it to obtain an organic-inorganic composite membrane. Scrape the organic-inorganic composite membrane off the petri dish, grind it, and obtain powder. (3) The powder obtained in step (2) is placed in a tube furnace and calcined in an Ar / H2 atmosphere to obtain an ordered mesoporous molybdenum disulfide material. The calcination in an Ar / H2 atmosphere is to first heat the material to 350-500℃ at a heating rate of 5-10℃ / min and calcinate it for 1-3 h. The amphiphilic block copolymer is one of polystyrene-ethylene oxide, polybutadiene-ethylene oxide, polystyrene-poly4-vinylpyridine, polyethylene oxide-polymethyl methacrylate, and polyacrylic acid-polystyrene; the ordered mesoporous molybdenum disulfide material has a pore size of 5-40 nm and a mesopore wall size of 2-10 nm.

2. The preparation method according to claim 1, characterized in that, The amphiphilic block copolymer has a hydrophilic segment with a molecular weight of 2500-5000 g / mol and a hydrophobic segment with a molecular weight of 2500-37500 g / mol.

3. The preparation method according to claim 1, characterized in that, In step (2), the evaporation temperature is 40-60℃ and the evaporation time is 12-24 h. The drying and curing temperature is 100-150℃ and the drying and curing time is 12-24 h.

4. The ordered mesoporous molybdenum disulfide material obtained by the preparation method according to any one of claims 1-3.

5. The application of the ordered mesoporous molybdenum disulfide material according to claim 4 in the preparation of gas sensors, photocatalysis, and photoelectric detection.

Citation Information

Patent Citations

  • Preparation method of transition metal sulfide catalytic material and catalytic application thereof

    CN101658792A

  • Resol-assisted synthetic large aperture ordered mesopore metallic oxide material and preparation method of material

    CN105129856A